Cardiovascular screening of elderly athletes - Robert Skalik; Anna Janocha (Nofer Institute of Occupational Medicine, 2024)
The permanently growing interest in amateur and professional sports activities among young, middle-aged and elderly athletes raises serious concerns about athletes' health, the safety of physical training, and the sports-related risk of sudden cardiac death and other cardiovascular complications during exercise. In recent years there has been an increasing number of cases of sudden cardiac death during physical effort. At present, life expectancy in the most developed countries grows rapidly and the number of people >65 years dramatically increases. Moreover, biological age of the population is lower. Subsequently, relevant increase in the number of elderly athletes involved in various types of sports activities has been reported in many countries. It was also demonstrated that physical activity has strong beneficial effect on cognitive functions, psychomotor performance and thus exercise capacity, which is very important for the elderly people in their everyday routine activities. Nonetheless, it should be remembered that participation in amateur and professional sports activities may be associated with risk of serious cardiovascular events in the elderly athletes often suffering from various civilization diseases. It is also reported that the number of elderly people after interventional cardiology procedures, open heart surgery and cancer treatment (chemotherapy, radiotherapy), who wish to participate in various sports activities, systematically grows. The authors of the paper conduct a literature review on cardiovascular risk assessment in the elderly athletes including the contemporary cardiology diagnostic methods and diagnostic schemes to prevent sudden cardiac death and other cardiovascular events during exercise. The controversies over efficacy of particular diagnostic tools to detect cardiovascular diseases in the elderly athletes and worldwide epidemiologic data concerning risk of sudden cardiac death during physical exercise have been also presented. Here, the authors have derived suggestions for establishment of comprehensive diagnostic schemes to prevent sudden cardiac death during sports activities. Med Pr Work Health Saf. 2024;75(3):233-241